A produção capitalista no/do espaço rural-urbano : o caso do povoado Flechas em Itabaiana/Sergipe - Cunha, Franciely Santos (2022)
The present dissertation has as its theme the study of the space production process in the capitalist mode of production, through the articulation between the real estate market and financial capital in peri-urban areas. In this context, in its logic of accumulation and expansion of profit, the capitalist mode of production needs to create new spaces, as well as adapt and recreate existing spaces. The Marxist capitalist analysis under the triad: landowners, real estate developers and the State in the production of space points to the transformation of the city as a business. In its expansion process, capital makes use of different action strategies. In ruralurban areas, one of the ways found by capital to continue reproducing itself is through the action of real estate finance capital, consequently, real estate speculation promoted in rural areas alters social relations and promotes the alienation of subjects in the production of space. From this perspective, the present study has the general objective of analyzing the process of expansion of real estate financial capital in rural-urban areas, having as its study area the Povoado Flechas in Itabaiana/SE. In the areas bordering the aforementioned Village, the launch and implementation of Santa Mônica I and II. Subdivisions has been observed in recent years. Such an enterprise establishes a dialectical relationship in the rural-urban space, fostered by the process of capital accumulation. To achieve the proposed objective, the historical and dialectical materialism method was chosen, which makes it possible to understand how the inherent contradictions of the capitalist mode of production materialize in the production of space. As methodological procedures, we used bibliographic research, documental research, fieldwork and photographic records. The transformations produced in space guarantee the logic of capital accumulation, allowing the continuity of the capitalist mode of production, characterized by contradictions and inequalities imposed both on the countryside and on the city.